Anti-Apoptosis of Podocytes and Pro-Apoptosis of Mesangial Cells for Telmisartan in Alleviating Diabetic Kidney Injury - Wei, Xin; Ma, Yabin; Li, Ya; Zhang, Wenzhao; Zhong, Yuting; Yu, Yue; Zhang, Li-Chao; Wang, Zhibin; Tu, Ye (Frontiers in Pharmacology, 2022)
Podocytes damage and mesangial cells expansion are two important pathological manifestations of glomerular injury in early diabetes. Telmisartan, as an angiotensin type 1 (AT1) receptor inhibitor, has been reported to improve advanced glycation end (AGE) products or angiotensin Ⅱ (Ang Ⅱ)-induced podocytes injury including detachment or apoptosis. In the current study we first confirmed the protective effect of telmisartan on early diabetic kidney injury in type 1 diabetic rats. Telmisartan reduced the loss of podocin and inhibited the expression of α-SMA, reflecting its protective effect on podocyte injury and mesangial proliferation, respectively. More interestingly we observed an opposite effect of telmisartan on the cell viability and apoptosis of podocytes and mesangial cells in a high-glucose environment in vitro. The anti-apoptotic effect of telmisartan on podocytes might be related to its inhibition of swiprosin-1 (a protein can mediate high glucose-induced podocyte apoptosis) expression. While telmisartan induced a high expression of PPARγ in mesangial cells, and GW9662 (a PPARγ antagonist) partially inhibited telmisartan-induced apoptosis and reduced viability of mesangial cells. In addition, high glucose-induced PKCβ1/TGFβ1 expression in mesangial cells could be blocked by telmisartan. These data provide a more precise cellular mechanism for revealing the protective effect of telmisartan in diabetic kidney injury.